LVA for Advanced Unilateral Lower Extremity Lymphedema: Impact of ICG Lymphography of Normal Side in Improving the Lymphatic Detection Rate and Operative Time - Abdelfattah, Usama; Elbanoby, Tarek; Omarah, Mona; Abdelmaksoud, Saber M.; Allam, Eatmad; Monir, Serag (Archives of Plastic Surgery, 2025)
Background Indocyanine green (ICG) lymphography has limited use in the detection of functioning lymphatics in advanced lymphedema. This study presents the use of normal-side ICG lymphography to navigate the potential sites of functional lymphatics and reports its impact on the lymphatic detection rate and operative time.Methods This was a retrospective study of unilateral lower extremity late-stage II or III lymphedema patients who underwent lymphaticovenous anastomosis (LVA) between February 2018 and June 2022.Markings for possible lymphatic vessels were made on the affected side solely in the early group (2018–2019) and on both the affected and normal side in the late group (2020–2022) using ICG lymphography.Results Between 2018 and 2022, 86 patients had complete data for analysis. Dermal backflow stage III was present in 5 limbs (5.81%), stage IV in 40 limbs (46.51%), and stage V in 41 limbs (47.67%). The late group had a higher mean lymphatic detection rate, which was statistically significant in the proximal leg incision site (2.05 ± 0.91 vs. 0.74 ± 0.82; p = 0.041). There was a significant tendency toward lower total LVA operative time per limb in the late group, which was led by the normal side mapping, with a mean operative time of 158 ± 14.88 minutes compared with 199 ± 12.45 minutes in the early group (p = 0.035).Conclusion Mirroring the affected limb by utilizing the normal-side ICG lymphography in guiding the incision sites for LVA could improve the lymphatic detection rate, minimize the number of incisions, and shorten the operative time.
Keywords: LVA; advanced lymphedema; lower extremity